2013
DOI: 10.2174/2211536611302010007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarkers for Inflammatory Diseases

Abstract: MicroRNAs (miRNAs), a class of small, non-coding RNA molecules with gene regulatory functions, have emerged to play a critical role in the pathogenesis of a variety of diseases. Current technological advances allow accurate, high throughput profiling of miRNA abundance in different tissues. More recently, extracellular, circulating miRNAs have begun to be demonstrated as highly stable, blood-based biomarkers for diseases. Understanding the interactions between circulating miRNAs and clinical phenotypes can enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 94 publications
(128 reference statements)
0
67
0
Order By: Relevance
“…miRNAs are endogenous small (19-24 nucleotides) noncoding RNAs that regulate gene expression through base-pairing to complementary sites in the 3′-untranslated region (UTR) of target messenger RNAs (mRNAs), leading to translational repression or degradation of the target mRNAs. 7,8 At least 50% of miRNAs are aberrantly expressed in many tumours, have important roles as post-transcriptional regulators and exhibit oncogenic or tumour suppressive functions by directly binding to target mRNAs. 9 Several miRNA databases such as Targetscan (http://www.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are endogenous small (19-24 nucleotides) noncoding RNAs that regulate gene expression through base-pairing to complementary sites in the 3′-untranslated region (UTR) of target messenger RNAs (mRNAs), leading to translational repression or degradation of the target mRNAs. 7,8 At least 50% of miRNAs are aberrantly expressed in many tumours, have important roles as post-transcriptional regulators and exhibit oncogenic or tumour suppressive functions by directly binding to target mRNAs. 9 Several miRNA databases such as Targetscan (http://www.…”
Section: Introductionmentioning
confidence: 99%
“…A study proved that circulating miRNAs have begun to be demonstrated as highly stable, blood-based biomarkers for diseases [15]. It is reported that miR-155 were induced in the human monocytic cell line THP-1 by LPS [16].…”
Section: Discussionmentioning
confidence: 99%
“…CmiRNAs are so remarkably stable that they can be specific to certain physiological and pathological conditions (Mitchell et al, 2008; Mi et al, 2013). The biological relevance of cmiRNAs is regarded as a global, hormone-like functional mechanism that might allow regulation of gene expression across tissues at a distance (Turchinovich et al, 2013).…”
Section: Discussionmentioning
confidence: 99%